PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH MELALUI MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION - Fitriana, Aprilia Nur (Indonesian Journal of History Education, 2014)
Learning is successful when students are able to comprehend what has been received. The use of learning models not only help teachers to teach but also help students understand the material being studied. Results of preliminary observations in High School 2 Magelang data showed that the students of class XI Social 2 still has a problem with activity and learning outcomes for the subjects of history. Mastery learning class XI Social 2 High School 2 Magelang prior to the study of 32.5%, so the learning activities of students is still low. The purpose of this study was to determine whether the application of learning models Cooperative Integrated Reading and Composition can increase the activity and student learning outcomes in history courses can class XI Social 2 High School 2 Magelang 2013/2014 school year.Â  Pembelajaran dikatakan berhasil ketika siswa dapat memahami apa yang telah diterimanya. Penggunaan model pembelajaran tidak hanya membantu guru dalam mengajar tetapi juga memudahkan siswa dalam memahami materi yang dipelajari. Hasil observasi awal di SMA Negeri 2 Magelang diperoleh data bahwa siswa kelas XI IPS 2 masih memiliki masalah dengan aktivitas dan hasil belajar untuk mata pelajaran sejarah. Ketuntasan belajar siswa kelas XI IPS 2 SMA Negeri 2 Magelang sebelum dilakukan penelitian sebesar 32,5%, sehingga aktivitas belajar siswa masih rendah.Â  Tujuan penelitian ini adalah untuk mengetahui apakah dengan penerapan model pembelajaran Cooperative Integrated Reading and Composition dapat meningkatkan aktivitas dan hasil belajar siswa pada mata pelajaran sejarah dapat kelas XI IPS 2 SMA Negeri 2 Magelang tahun pelajaran 2013/2014. Â